Assessment of Aspartate and Bicarbonate Produced From Hyperpolarized [1-13C]Pyruvate as Markers of Renal Gluconeogenesis - Yoshihara, Hikari A. I.; Comment, Arnaud; Schwitter, Juerg (Frontiers in Physiology, 2021)
As both a consumer and producer of glucose, the kidney plays a significant role in glucose homeostasis. Measuring renal gluconeogenesis requires invasive techniques, and less invasive methods would allow renal gluconeogenesis to be measured more routinely. Magnetic resonance spectroscopy and imaging of infused substrates bearing hyperpolarized carbon-13 spin labels allows metabolism to be detected within the body with excellent sensitivity. Conversion of hyperpolarized 1-13C pyruvate in the fasted rat liver is associated with gluconeogenic flux through phosphoenolpyruvate carboxykinase (PEPCK) rather than pyruvate dehydrogenase (PDH), and this study tested whether this was also the case in the kidney. The left kidney was scanned in fed and overnight-fasted rats either with or without prior treatment by the PEPCK inhibitor 3-mercaptopicolinic acid (3-MPA) following infusion of hyperpolarized 1-13C pyruvate. The 13C-bicarbonate signal normalized to the total metabolite signal was 3.2-fold lower in fasted rats (p = 0.00073) and was not significantly affected by 3-MPA treatment in either nutritional state. By contrast, the normalized [1-13C]aspartate signal was on average 2.2-fold higher in the fasted state (p = 0.038), and following 3-MPA treatment it was 2.8-fold lower in fed rats and 15-fold lower in fasted rats (p = 0.001). These results confirm that, unlike in the liver, most of the pyruvate-to-bicarbonate conversion in the fasted kidney results from PDH flux. The higher conversion to aspartate in fasted kidney and the marked drop following PEPCK inhibition demonstrate the potential of this metabolite as a marker of renal gluconeogenesis.